Phytophthora species detected in the rhizosphere of Alnus glutinosa stands in the Floodplain Forests of Western Turkey - Kaya, Ayse Guelden Aday; Lehtijaervi, Asko Tapio; Sasmaz, Yusuf; Nowakowska, Justyna A.; Oszako, Tomasz; Lehtijaervi, Hatice Tugba Dogmus (Wiley, 2018)
The occurrence of Phytophthora species in Alnus glutinosa stands in the Karacabey and Igneada floodplain forests was investigated. Twenty-seven soil samples taken from the rhizosphere of declining trees (without bark symptoms) were baited for Phytophthora. In total, 311 Phytophthora isolates were obtained following culturing on selective medium. On the basis of the morphological characteristics and the ITS sequences of the rDNA, Phytophthora plurivora accounted for 83% of the rhizosphere isolates. In addition to P. plurivora, P. gonapodyides (9%), P. chlamydospora (3.8%), P. lacustris (2.5%) and P. aff. cactorum (2%) were isolated from the surveyed areas. No P. x alni was detected in the present work. This paper is the first to report the isolation of P. plurivora and P. aff. cactorum from the rhizosphere of Alnus species in Turkey.
Keywords: [No Keywords]